Opportunities for International Phonetic Alphabet application to the sounds of Lithuanian dialects - Bakšienė, Rima; Čepaitienė, Agnė (Baltistica, 2017)
The paper discusses the issues of transcription of Lithuanian dialects. It compares the International Phonetic Alphabet (IPA) with the characters of the currently popular font Palemonas.From the 20th to the 21st century, almost for a whole century, there has been a tradition in Lithuania to mark texts of Lithuanian dialects using the so-called Copenhagen transcription that was adapted by Georg Gerullis. The established Lithuanian transcription system largely differs from those applied in other languages, even from the closest neighbours Latvians. Therefore, researchers are often confronted with the problems of comparing the research results of several languages. In the 21st century the issues of different transcriptions became more relevant after quantitative measurements of language variance became popular. They are usually made by computer programs which require identical data.The discussion paper analyses the opportunities for IPA application to the sounds of Lithuanian dialects, discusses the marking correspondences of vowels, consonants, some phonetic features and prosodic units in the font Palemonas and IPA, and provides examples of words from various Lithuanian subdialects transcribed by applying both systems.
Keywords: Lithuanian dialects; phonology; International Phonetic Alphabet (IPA); transcription; vocalism; consonantism; prosody